Synthesis, Characterization and Antimicrobial Evolution of New Bi-α-amino Nitrile Compounds - Abdulhameed, Zena; J. Alabdali, Ammar (Al-Nahrain Journal of Science, 2024)
This project is regarding the synthesis of  new bi-α-amino nitrile compounds derived from the reaction of di-amine , aldehyde (vanillin  or  o-vanillin ), and KCN in glacial acetic acid as a solvent . The three components-one pot reaction  produced (2, 2' - (1, 2-phenylenebis (azanediyl)) bis(2-(4-hydroxy-3-methoxyphenyl) acetonitrile) (I) and (2, 2'-(1, 2- phenylenebis (azanediyl)) bis(2-(2-hydroxy-3-methoxyphenyl) acetonitrile) (II) considering the formation of bi-imine compounds as intermediate. α-amino nitrile compounds (I and II)  were characterized using infrared spectroscopy and mass spectroscopy. The prepared compounds were screened for their anti-microbial activity. The bacteria are Gram positive (Staphylococcus aurous) and Gram negative (Escherichia coli) in vitro, the results were promising; due to the large inhibition zones.